State Controllability Analysis for Irreversible Systems Using Set Theory - L.M. Gómez; H. Botero; H. Álvarez; Fernando di Sciascio (Revista Iberoamericana de Automática e Informática Industrial RIAI)
The irreversible systems have been little studied within the control theory framework, although one of their relevant cases is the batch process control problem. Therefore, in this work a method for analysing state controllability of irreversible systems is proposed. The method uses set theory and its extension to batch processes. Definitions for Reversible Set and Controllable Trajectories Set, both for nonlinear systems, are given in order to analyze state controllability for irreversible systems. Additionally, an algorithm for calculating mentioned sets from the dynamic process knowledge is proposed. The proposal is applied to a batch process benchmark. Obtained simulation results demonstrate the advantages of that proposal to analyze the state controllability of irreversible systems.